2016
DOI: 10.1016/j.ymben.2016.03.007
|View full text |Cite
|
Sign up to set email alerts
|

l -Lysine production independent of the oxidative pentose phosphate pathway by Corynebacterium glutamicum with the Streptococcus mutans gapN gene

Abstract: We have recently developed a Corynebacterium glutamicum strain that generates NADPH via the glycolytic pathway by replacing endogenous NAD-dependent glyceraldehyde 3-phosphate dehydrogenase (GapA) with a nonphosphorylating NADP-dependent glyceraldehyde 3-phosphate dehydrogenase (GapN) from Streptococcus mutans. Strain RE2, a suppressor mutant spontaneously isolated for its improved growth on glucose from the engineered strain, was proven to be a high-potential host for L-lysine production (Takeno et al., 2010)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 37 publications
0
17
1
Order By: Relevance
“…We also found that some genes related to metabolism and growth in plants were downregulated by the D50 irrigation regime, including CAD1 , UGT90A1 , UGT74E2 , UGT92A1 , GAPN , PsbW , and PSB28. UGT74E2 was involved in water stress response in Arabidopsis plant through its activity to auxin indole-3-butyric acid ( IBA ) [ 63 ]; GapN catalyzes the oxidation of glyceraldehyde 3-phosphate to 3-phosphoglycerate and is an alternative NADPH source [ 64 , 65 ]; PsbW and PSB28 are involved in the stabilization and recovery of photosystem II complexes, respectively [ 66 , 67 ]. The downregulation of these genes in response to the D50 irrigation regime compared with the D30 irrigation regime might reveal the disturbance of photosystem II systems and the energy source by the D50 regime.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that some genes related to metabolism and growth in plants were downregulated by the D50 irrigation regime, including CAD1 , UGT90A1 , UGT74E2 , UGT92A1 , GAPN , PsbW , and PSB28. UGT74E2 was involved in water stress response in Arabidopsis plant through its activity to auxin indole-3-butyric acid ( IBA ) [ 63 ]; GapN catalyzes the oxidation of glyceraldehyde 3-phosphate to 3-phosphoglycerate and is an alternative NADPH source [ 64 , 65 ]; PsbW and PSB28 are involved in the stabilization and recovery of photosystem II complexes, respectively [ 66 , 67 ]. The downregulation of these genes in response to the D50 irrigation regime compared with the D30 irrigation regime might reveal the disturbance of photosystem II systems and the energy source by the D50 regime.…”
Section: Discussionmentioning
confidence: 99%
“…GapN was also valuable for increasing lysine production from glucose in C. glutamicum because it provided an extra source of NADPH (Takeno et al, 2010). More recently, it was discovered that GapN could even compensate for the absence of the oxidative PP pathway, which is normally the major source of NADPH in C. glutamicum (Takeno et al, 2016). A similar benefit was seen with mannitol as the substrate.…”
Section: Toward Optimum Lysine Production At Low Pp Pathway Fluxesmentioning
confidence: 97%
“…Therefore, balancing the oxidation–reduction state of NAD(H/ + ) and NADP(H/ + ) is crucial for both catabolism and anabolism. Some examples have illustrated the importance of redox balance and availability for producing the fine chemicals including amino acids [79], vitamins [10, 11] and lipids [12, 13]. l -Lysine, as an essential amino acid for animals and humans, is mainly produced by C. glutamicum or its derivatives, which were created by traditional mutagenesis-screening techniques or by genetic engineering [14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…l -Lysine, as an essential amino acid for animals and humans, is mainly produced by C. glutamicum or its derivatives, which were created by traditional mutagenesis-screening techniques or by genetic engineering [14, 15]. Notably, 4 mol of NADPH must be supplied for 1 mol of l -lysine biosynthesis from oxaloacetate, and thus numerous studies have focused on engineering the metabolism of NADPH for improving l -lysine producing strains [9, 1619]. For example, genetic modification of the native glyceraldehyde-3-phosphate dehydrogenase (GAPDH) has been proven to improve the l -lysine production because of the increase of NADPH availability [17, 19, 20].…”
Section: Introductionmentioning
confidence: 99%